Some Indispensable Theological Questions about Darwin’s Work and Testimony - SZENTPÉTERY, Péter (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
The author gives a summary based on his habilitation thesis and other works on the origin of Darwin’s theory of evolution and the theological questions raised by it. Even if the assumed mechanism of the origin of living beings (and of life) has changed much since the publishing of the Origin (1859), the basic theological questions must always be asked anew. Darwin himself was not an atheist but an agnostic, more or less deist according to his own confession. He could not fully explain away the Creator but tried to minimize his role because of the evil in nature, i.e. the problem of theodicy. Ironically, even if certain questions raised by the theory/doctrine of evolution seem quite logical and obvious, they are often neglected or omitted in theological works on creation. It is not enough to say that creation and evolution are compatible because the fact of creation and the method of creation should be discerned: one is a religious belief/testimony and the other a scientific theory. The real question is whether and how the supernatural can be detected. To believe in the resurrection of Christ and humans has any meaning only on condition that this present life subject to death is of supernatural origin without any alternative. The whole Scripture teaches this definitely: “Through him God made all things; not one thing in all creation was made without him” (John 1:3). Christian creation faith must be qualitatively different from “attaching” the Creator to the contemporary majority hypothesis of origin or “fitting” him into its framework. Ultimately, either one likes it or not, in questions of origin, humans are dependent on revelation.